PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIKIH DI KELAS I TMI PONDOK PESANTREN AL BASYARIYAH BANDUNG - Agustin, Usman usman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Jurisprudence learning is not just about providing material to students but must be able to become understanding and practice for students in everyday life. So many methods used in the learning process will give good results for students. One way to achieve good learning outcomes is by using the Active Learning method. There is no exception to the application of the active learning model in improving student learning outcomes in class 1 Islamic jurisprudence lessons at TMI Al Basyariyah Islamic Boarding School Bandung with the type of research used is field qualitative research, using data collection techniques through observation, interviews and documentation. So that the researchers concluded that the process of applying active learning in improving student learning outcomes in science subjects in class 1 TMI Pondok Pesantren Al Basyariyah uses the steps of learning jurisprudence and the principles of active learning so that student learning outcomes become better